Traumatic Brain Injury: A Study from the Middle-East - Alfallaj, Muath Ibrahim; Salati, Sajad Ahmad (Lietuvos chirurgija, 2025)
Background. Traumatic head injuries represent one of the major causes of mortality and long-term disability worldwide. This main objective of this study was to explore the patterns, severity, and outcomes of these injuries. Methods. An observational, descriptive, retrospective study was carried out utilizing a validated data collection sheet, after attaining a proper ethical committee approval. Well-defined exclusion and inclusion criteria were applied. Results. There were 185 patients enrolled in the study, including 153 (82.7%) males and 32 (47%) females, with a mean age of 41.5 years. Road traffic accidents were the most frequent cause of injury, followed by falls, machinery-related accidents, and assaults. A conservative strategy was used to treat 101 (54.6%) of the patients, whereas various surgical procedures were performed on 84 (45.4%). Outcomes were related to Glasgow Coma score on presentation and favorable in 135 (73%) patients. Conclusions. Road traffic accidents and falls from heights are the leading causes of traumatic brain injury. As a result, preventive measures including road safety and workplace regulations must be addressed.